Presepsi Masyarakat Kajen dalam Penggunaan Jasa Tabungan Syariah di Wilayah Kabupaten Pekalongan - Selfi Nirmalasari; Siti Robiah; Muhammad Alief Fikri Dzikriansyah; Fiya Saadah Alma Fatih; Dyah Anindita Nur Wulandari (Journal of Islamic Economics and Finance, 2023)
As time goes by, economic activity in Indonesia certainly experiences development, as does the development of increasingly modern technology. This development also spread to Islamic banking. The beginning of the development of the Islamic finance industry was initiated by the inspiration of the Indonesian people, who are predominantly Muslim. The purpose of this study is to analyze how the perception of the Kajen community is related to sharia-based savings services in the Pekalongan Regency area. The method used in this study uses a qualitative approach with research subjects from the Kajen community based on a representative principle. Source of data in this study using primary data by using interviews with informants. The results of this study are that people already understand the existence of sharia savings services. Sharia savings institutions in the community include BSI, Bank Muamalat, BTM, BMT, BTN. According to public perception, sharia savings services have attractive performance and friendly service. However, there are several obstacles in terms of opening sharia savings, namely the many requirements that must be met.